A Study Of Malaysian Internet User's Motivations And Concerns: Online Shopping Perspectives - Mohd Suki, Norazah (2002)
Electronic Commerce ( E-Commerce0 growth is increasing at a rapid rate and is replacing traditional commerce. The benefits of shopping online cannot be underestimated. The E-Commerce offers Internet users a wider range of benefits, such as finding the products which cannot be available locally and reducing Internet users' time for searching the related products. Furthermore, the Internet users receive more attractive sales promotional offers from Internet sellers and also through individual email accounts. Despite these motivational factors, there are various transactional and non-transactional issue involved such as, Internet users being uncomfortable while giving their credit cards numbers on the Internet, Internet merchants' misuse of users' peersonal information, lack of help from sales representative whilst purchasing online and offer of products are in different currencies. These and other factors appear to affect emerging trends of Electronic Commerce in Malaysia. This study therefore, focuses on providing a deeper insight into the factors that may motivate Malaysian Internet users' browsing or purchasing through the iNternet and also the concern factors, which affect the online buyers. This study seeks to identify the Internet users' frequency of placing orders on the Internet. Also to assess the number of hours spent per day when purchasing or browsing through the Internet as well as to test the relationship between motivation and concern factors with respect to demographic factors. Among the survey findings were: privacy, quality, payment, connection speed, trust and reluctant to change were the important factors discriminating much on Internet users' length of Internet usage, ownership of credit cards and frequency of online buying. Those six factors are the contributing factors inhibiting Malaysian Internet users to conduct online shopping. Interestingly, most of the motivation factors like accessibility, availability, distribution, searcharbility, and socialisation also contribute much discrimination for Malaysian Internet users to shop online. Therefore, electronic transactions should be secure, reliable, and trusted in order to attract and maintain existing users of the Internet. Such measures would increase Internet users confidence on the credibility of Internet sellers. Overall, this research study has added to the growing number of published research findings on the latest scenarios on emerging trends of Electronic commerce in Malsysia to date, with regards to online shopping activities.